Kinerja Karyawan Dipengaruhi Mediasi Kepuasan kerja Melalui Beban Kerja dan Servant Leadership - Adam Damiri; Wawan Prahiawan; Ali Imron Imron (LP2M Universitas Ibrahimy, 2025)
This study aims to determine how servant leadership (X₂) and workload (X₁) at PT. Hiu Megaptera Tangerang City impact worker performance (Y) through job satisfaction (Z). This study employed a quantitative approach using a descriptive methodology. The study's population consisted of 85 workers from PT. Hiu Megaptera. The research sample is a saturated sample, meaning that all 85 employees of PT Hiu Megaptera are included in the sample. Structural Equation Modelling SmartPLS 4.0 analysis, this tool is analyize method used in this research. based on findings of the hypothesis, it was investigated in this study. Performance is positively and significantly impacted by both servant leadership and workload.